Aspects of the biology of a house sparrow (Passer domesticus) colony - Wetton, Jon (1990)
Morphological, biochemical and minisatellite DNA variation was investigated at the colour ringed Brackenhurst House Sparrow population. Measurements and blood samples were collected from 584 nestlings and 692 other birds between 1985 and 1989. Six loci (6PGD, IDH, PEPD2, PEPD3, PEPT and transferrin) which had been the subject of a previous report (Burke, 1984) were investigated by starch gel electrophoresis. All followed Mendelian inheritance patterns, were in Hardy Weinberg equilibria and displayed temporal stability in allele frequencies. No evidence was found of the previously reported segregation distortion at PEPD3 and transferrin but artefact bands were encountered when scoring the latter.